Washback of an English language assessment system in a Malaysian university foundation programme - Bokiev, Umed; Abd. Samad, Arshad (Nova Southeastern University, 2021)
Washback refers to the influence of language assessment on teaching and learning. In contrast to the wealth of studies involving external large-scale language examinations, scant research has been conducted to explore the influence of internal language assessment on instruction, particularly in the context of a university foundation programme. This qualitative study investigated the washback effects of an English language assessment system (ELAS) on the teaching and learning of English in a Malaysian university foundation programme. Apart from an in-depth analysis of official documents on the ELAS, we conducted individual semi-structured interviews with three curriculum and assessment developers, three English language instructors, four students and four alumni of the foundation programme and analysed the collected data using Miles and Huberman’s (1994) framework for qualitative data analysis. Findings indicated that the ELAS, with its different assessment forms, exerted an overall positive washback on various aspects of English teaching and learning. Yet, a number of factors related to the assessment, teachers, students as well as context mediated the extent of washback experienced. Based on the findings of the study, we put forward a few recommendations on how to encourage positive washback.